"Reframing" relation-based practice in the child protection sector in remote Aboriginal communities of Australia. Issue 3 (3rd July 2018) - Nietz, Heidi
Abstract : Australia, like other post-colonial countries, witnesses an over-representation of Indigenous children in the child protection sector and the trend continues to rise. International indigenous scholarship in child protection seeks to problematise relation-based practice to instantiate decolonising standards. However, much of this transformative agenda is situated in psychosocial approaches that focus on inherent power relations and thereby jettison strategies enabling social workers to engage in emotional learning to contain their defences against anxieties. An autoethnography of practice stressors in remote Aboriginal Australian communities is provided and a call for the restoration of relational psychodynamics as the most responsive form to decolonising practice standards.